2010
DOI: 10.5851/kosfa.2010.30.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kimchi Powder on Quality Characteristics of Semi-dried Pork Jerky

Abstract: This study was carried out to investigate the effects of kimchi powder addition on the quality properties of semi-dried pork jerky. Jerky was unamended (control) or was amended with dried kimchi powder to a concentration of 1% (T1), 2% (T2) or 3% (T3). The contents of moisture and ash were the highest in the T3 treatment. The protein content was highest in the control, but there was no significant difference in the fat content. The control exhibited the highest pH value, whereas T2 exhibited the lowest metmyog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…These results agree with those of Thebaudin et al (1997), who indicated that the hardness of the meat product were improved when dietary fiber was added to the formulation. An et al (2010) reported that the hardness of semi-dry jerky decreased with the addition of kimchi fiber. According to García et al (2002), the presence of fruit fiber decreases the hardness of sausage because the fruit fiber reduces the water loss thus lowering the hardness.…”
Section: A -Dmentioning
confidence: 99%
“…These results agree with those of Thebaudin et al (1997), who indicated that the hardness of the meat product were improved when dietary fiber was added to the formulation. An et al (2010) reported that the hardness of semi-dry jerky decreased with the addition of kimchi fiber. According to García et al (2002), the presence of fruit fiber decreases the hardness of sausage because the fruit fiber reduces the water loss thus lowering the hardness.…”
Section: A -Dmentioning
confidence: 99%
“…The presence of antioxidants resulted in a significant decrease (16.25-18.47%) in the amounts of metmyoglobin developed during storage which was attributed to the strong antioxidant activity. An et al [19] evaluated the percent metmyoglobin of the pork jerky samples incorporated with different kimchi powder concentrations. It has been reported that the metmyoglobin contents (%) of the samples prepared with various kimchi powder levels (ranged from 81 to 83%) were significantly ( < 0.05) lower than that of control sample (85%) [19].…”
Section: Metmyoglobin Content Assaymentioning
confidence: 99%
“…An et al [19] evaluated the percent metmyoglobin of the pork jerky samples incorporated with different kimchi powder concentrations. It has been reported that the metmyoglobin contents (%) of the samples prepared with various kimchi powder levels (ranged from 81 to 83%) were significantly ( < 0.05) lower than that of control sample (85%) [19]. There was no significant difference between the amounts of metmyoglobin under the influence of natural extracts or BHT indicating that these natural extracts can be utilized as a substitute for BHT to prevent discoloration.…”
Section: Metmyoglobin Content Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Supposedly, this result is attributable to both the fact that dietary fiber lowers blood sugar by delaying absorption of sugar and also due to very low GI and antioxidant effects of stevioside used as a sugar substitute. It has been known that addition of antioxidant substances containing polyphe- [1][2][3][4][5] Abbreviations are the same as Table 1.…”
Section: Texture Analysis and Sensory Evaluationsmentioning
confidence: 99%